Cardiovascular Manifestations of COVID-19 - Altamimi, Hasan (Heart Views, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is the cause of COVID-19, was first reported in Wuhan, China. SARS-CoV-2 especially involves alveolar epithelial cells, which results in respiratory symptoms more severe in patients with cardiovascular disease (CVD) probably linked with increased secretion of angiotensin-converting enzyme 2 in these patients compared with healthy individuals. Cardiac manifestations may contribute to overall mortality and even be the primary cause of death in many of these patients. A higher prevalence of hypertension (HTN) followed by diabetes mellitus and CVD was observed in COVID-19 patients. A higher case-fatality rate was seen among patients with pre-existing comorbid conditions, such as diabetes, chronic respiratory disease, HTN, and cancer, compared to a lesser rate in the entire population. Cardiovascular (CV) manifestations of COVID-19 encompass a wide spectrum, including myocardial injury, infarction, myocarditis-simulating ST-segment elevation myocardial infarction, nonischemic cardiomyopathy, coronary vasospasm, pericarditis, or stress (takotsubo) cardiomyopathy. This review is intended to summarize our current understanding of the CV manifestations of COVID-19 and also to study the relationship between SARS-CoV-2 and CVDs and discuss possible mechanisms of action behind SARS-CoV-2 infection-induced damage to the CV system.